Hambatan Pelayanan BK di Luar Jam Pelajaran dan Upaya Mengatasinya di SMA Kabupaten Brebes - Prasetyaningtyas, Noviana; Sugiharto, DYP; Suharso, Suharso (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
This study aims to determine the barriers in the implementation of guidance and counseling services outside school hours in the school as Brebes and how efforts to overcome them. Type of research is descriptive research with survey method. The population in this study were all high school counselors as Brebes implementing guidance and counseling services outside school hours to 78 counselors. The research sample using cluster sampling is 30 counselors. Data was collected using questionnaires. Percentage of descriptive data analysis techniques. The results showed the percentage level of resistance for counselor competencies 72% in the high category, creativity counselor 73% higher, 79% higher work motivation, 75% of high school principals, teachers of 66% medium, perceptions and interests of students and 77% higher infrastructure 71% higher.